Design Considerations for the Development and Implementation of a Medical Respite for Older Adults Experiencing Homelessness in Metro Vancouver. Issue 4 (April 2021) - Canham, Sarah L.; Humphries, Joe; Danielsen, Chris; Small, Scott; Bosma, Harvey
Abstract : Background: Older persons with lived or living experience of homelessness (PWLEs) often live with complex physical and/or mental health conditions which are challenged by poor access to health services, especially primary care. To fill the gap in the continuum of care following hospital discharge for PWLEs, medical respite provides health and shelter support for PWLEs who do not have acute care needs that qualify for a stay in a hospital bed, yet are too sick or frail to recover on the streets or in a traditional shelter. Objective: This study examines how a medical respite could be designed for older PWLEs in Metro Vancouver, BC. Research Design: Using a community-based participatory research approach, in-depth interviews and focus groups were conducted with PWLE (n=15) and service provider (n=11) participants. Results: Participants offered rich suggestions about (a) the culture of the medical respite, (b) the physical design of a medical respite, (c) individuals who should be involved in medical respite delivery, (d) services a medical respite should provide, and (e) who the medical respite should serve. Conclusions: When designing a medical respite for older PWLEs, considerations include providing an environment where patients can rest, but also feel safe and be surrounded by persons who they trust and who care for them. Developing a medical respite that adheres to the tenets of trauma-informed and patient-centered care acknowledges the mistrust and traumatization that often accompanies homeless patients presenting to health care. Abstract : Supplemental Digital Content is available in the text.